2022
DOI: 10.3389/fenrg.2022.879373
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Sizing Grid-Connected Hybrid PV/Generator/Battery Systems Following the Prediction of CO2 Emission and Electricity Consumption by Machine Learning Methods (MLP and SVR): Aseer, Tabuk, and Eastern Region, Saudi Arabia

Abstract: Researchers’ concentration has been on hybrid systems that can fulfill economic and environmental goals in recent years. In this study, first, the prediction of CO2 emission and electricity consumption of Saudi Arabia by 2040 is made by employing multi-layer perceptron (MLP) and support vector regression (SVR) methods to see the rate of CO2 emission and electricity consumption. In this regard, the most important parameters such as gross domestic product (GDP), population, oil consumption, natural gas consumpti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…In contrast to Albogamy et al (2022), Almutairi et al (2022), Liu et al (2022), Saxena et al (2022), Zaidan et al (2022), it was found that Smart Grid mainly depends on government governance, which includes both infrastructure support, and regulation of the energy economy. The role of corporate governance is secondary.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…In contrast to Albogamy et al (2022), Almutairi et al (2022), Liu et al (2022), Saxena et al (2022), Zaidan et al (2022), it was found that Smart Grid mainly depends on government governance, which includes both infrastructure support, and regulation of the energy economy. The role of corporate governance is secondary.…”
Section: Discussionmentioning
confidence: 96%
“…The publications of Albogamy et al (2022), Almutairi et al (2022), Liu et al (2022), Saxena et al (2022), Zaidan et al (2022) suggest the functioning and development of Smart Grid based on corporate governance with a secondary role of the state. Smart Grid is interpreted as a high-tech innovation of energy companies.…”
Section: Smart Grid As a Vector Of Energy Economy Developmentmentioning
confidence: 99%
“…The second category is when consumption is less 1-6000 kWh, with the rate charge of at 0.048 USD/kWh. Based on these categories, these new rates were used to schedule the fixed prices at various times during the day as explained in [35]. Figure 6 shows the considered grid-connected system in the research.…”
Section: Grid Parametersmentioning
confidence: 99%